Selecting a commercial clinical information system: an academic medical center's experience. - Wong, E. T. (American Medical Informatics Association, 1994)
Choosing a commercial clinical information system to meet the information needs of patient care, research, education, administration, finance, and ongoing changes of the healthcare system of an academic medical center is a challenging task. For the past six months, The Milton S. Hershey Medical Center undertook this task through (i) establishing a task force, (ii) assessing end-user information needs, (iii) understanding future institutional development and strategies, (iv) conceptualizing the ideal system, (v) identifying a short list of vendors, (vi) sending RFIs to vendors, (vii) visiting vendors' headquarters, (viii) technical review, (ix) reference calls, (x) using consultation services, (xi) on-site demonstration, and (xii) visiting the vendor's clients.